Parallelization of the primitive equations for ocean circulation model using CPU-GPU platform - Abdullah Aysh Qasem Dahawi, 1985-, author; Norma Alias, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2015